2008
DOI: 10.1155/2008/185248
|View full text |Cite
|
Sign up to set email alerts
|

On the Evaluation of the Conversational Speech Quality in Telecommunications

Abstract: We propose an objective method to assess speech quality in the conversational context by taking into account the talking and listening speech qualities and the impact of delay. This approach is applied to the results of four subjective tests on the effects of echo, delay, packet loss, and noise. The dataset is divided into training and validation sets. For the training set, a multiple linear regression is applied to determine a relationship between conversational, talking, and listening speech qualities and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In particular, the situation of assessment in which the judging subject is placed (listening/viewing or conversational context referred as experimental context) can impact the judgement process [11]. Subjective tests should reflect the ecological environment of the service or application under assessment.…”
Section: Impact Of the Experimental Context On Perceived Audiovisual mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the situation of assessment in which the judging subject is placed (listening/viewing or conversational context referred as experimental context) can impact the judgement process [11]. Subjective tests should reflect the ecological environment of the service or application under assessment.…”
Section: Impact Of the Experimental Context On Perceived Audiovisual mentioning
confidence: 99%
“…Early studies on the impact of conversational delay on speech quality, like the one from Kitawaki and Itoh [8], predicted a severe impact of transmission delay on the perceived speech quality especially when considering highly interactive tasks like the 'Random Number Verification' task [9]. However, recent studies [10][11][12] suggested that the impact of delay in close-to-natural conversation scenarios is far less important as suggested in [8]. In the case of everyday life conversations, it was observed that people tend to adapt their communication strategy affecting both the structure and the semantic flow of the conversation (e.g., misunderstandings and interruptions).…”
Section: Introductionmentioning
confidence: 99%
“…It takes into account the impact of degradations such as talker echo, coding artifacts, and additive noise on the talker's perception of his/her own voice. Guéguin et al [20] proposed a signal-based model of conversational speech quality that combines both PESQ and PESQM with an estimation of the conversational impact of pure delay, the latter being derived from the E-model. None of these approaches has been standardized yet, but the definition and validation of a signal-based model for conversational speech quality is a work item in ITU-T Study Group 12.…”
Section: Reference-free Models Have Gained Much Attention Recently Asmentioning
confidence: 99%
“…In [9] an objective method to assess the speech quality in conversational context, based on both talking and listening qualities, including the impact of delay, is proposed. Two datasets are used: one for training and the other one for validation.…”
Section: Introductionmentioning
confidence: 99%